1995
DOI: 10.1006/viro.1995.1435
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and Antigenicity of Hepatitis B Virus Small Envelope Proteins Lacking Cysteines in the Major Antigenic Region

Abstract: Disulfide bonds are of crucial importance for the structure and antigenic properties of the hepatitis B virus (HBV) envelope. We have evaluated the role of the eight highly conserved cysteines of the major antigenic region for assembly, secretion, and antigenicity of the envelope proteins. Mutants carrying single or multiple substitutions of alanine for cysteine were analyzed using epitope tagging and transient expression in COS-7 cells. The only single cysteines found to be indispensable for efficient secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 0 publications
9
77
0
Order By: Relevance
“…The AGL is known to bear the major HBVneutralizing epitopes (30) and a conserved immunodominant determinant, referred to as "a." It also contains eight cysteine residues described as engaged in disulfide bonds that are in-strumental in defining the structure of the "a" determinant (25,27). Furthermore, cysteines at positions 121 and 124 constitute a CxxC motif that is generally found on protein-disulfide isomerase (PDI)-related proteins (38).…”
mentioning
confidence: 99%
“…The AGL is known to bear the major HBVneutralizing epitopes (30) and a conserved immunodominant determinant, referred to as "a." It also contains eight cysteine residues described as engaged in disulfide bonds that are in-strumental in defining the structure of the "a" determinant (25,27). Furthermore, cysteines at positions 121 and 124 constitute a CxxC motif that is generally found on protein-disulfide isomerase (PDI)-related proteins (38).…”
mentioning
confidence: 99%
“…A number of small deletions in the carboxyl part of CYL-I or that of the AGL were also detrimental for SVP production, but surprisingly, deletion of the entire AGL was tolerated for SVP secretion and seemed to affect only the mutant stability or its expression level (33). Mutational analysis of cysteine residues revealed that those located at positions 48, 65, and 69 in CYL-I and 107 in the AGL were essential for SVP secretion (30,31).…”
mentioning
confidence: 99%
“…Some previous studies observed that cysteine 69 was highly conserved and essential for HBsAg secretion from infected hepatocytes [25,26]. A stop codon mutation at this position may lead to the accumulation of the prematurely truncated form of HBsAg into the hepatocyte and may induce transactivation of cellular promoters, including those encoding oncogenic proteins.…”
Section: Discussionmentioning
confidence: 99%